2020
DOI: 10.1177/0886260520948145
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Violence and Factors Associated with Victimization among Female Entertainment Workers in Cambodia: A Cross-Sectional Study

Abstract: Women working in the entertainment industry are confronted with various forms of gender-based violence (GBV). However, their vulnerability remains understudied, particularly in resource-limited settings. This study aims to examine the prevalence of GBV among female entertainment workers (FEWs) in Cambodia and identify factors associated with victimization. We conducted a cross-sectional study in November 2018 for the impact evaluation of a randomized controlled trial. We used a stratified random sampling metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…We also found that 43% of female participants in this study worked in the entertainment sector compared to only 4% of men. Being female entertainment workers could be an underlying factor because a previous study among female entertainment workers in Cambodia showed a high prevalence of gender-based violence at work and its positive association with psychological distress [49]. This result implies that interventions to address mental health among people who use drugs should be gender-sensitive and focused on subpopulations with lower education and in occupations that expose them to underlying risks.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…We also found that 43% of female participants in this study worked in the entertainment sector compared to only 4% of men. Being female entertainment workers could be an underlying factor because a previous study among female entertainment workers in Cambodia showed a high prevalence of gender-based violence at work and its positive association with psychological distress [49]. This result implies that interventions to address mental health among people who use drugs should be gender-sensitive and focused on subpopulations with lower education and in occupations that expose them to underlying risks.…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…FEWs have an HIV prevalence of nearly 10% and low HIV and STI testing rates and service seeking [ 10 ]. They also have low rates of modern contraceptive use and high rates of induced abortion [ 8 , 11 ] and are frequent victims of GBV [ 7 , 12 ]. The rates are higher among FEWs younger than 30 years than among the older groups [ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to long work hours, low pay, and unhealthy working conditions, many women take higher-paying jobs offered by entertainment venues, where some may engage in selling sex to further increase their earnings (1). Despite the increased pay, FEWs in Cambodia are frequently victims of violence associated with their occupation, where 37.5% of FEWs report having experienced some types of violence the past six months, and more than half of FEWs report their clients as the main perpetrator (10).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, FEWs often report facing discrimination from providers when seeking health and support services (9). Additionally, their health access has been further exacerbated by the introduction of Cambodia's 2008 Law on the Suppression of Human Trafficking and Sexual Exploitation, which aimed to criminalized prostitution (10). In Cambodia, outlawing prostitution has ultimately amplified the stigma and discrimination associated with entertainment work and deterred FEWs from carrying condoms and reporting violence instances to the police (9,11,12).…”
Section: Introductionmentioning
confidence: 99%